INFORMATIZATION OF EDUCATION: PERSONAL ACCOUNT OF UNIVERSITY ELECTRONIC LIBRARY - Ruslan A. Baryshev; Olga I. Babina; Margarita M. Manushkina (Moscow Polytechnic University, 2016)
The article considers historical aspects of informatization at university, notes the key role of a library in the past and the loss of this role in modern universities. Decrease in demand of library services in university is stated. The issue reveals in the existence of a certain gap between the needs of students and the possibilities of university informational and educational services (including electronic library) to meet these needs. The article describes the experience of Siberian Federal University in the development of an automated information system based on the personal account technology.